Hubungan Pengetahuan Dan Sikap Pekerja Medis Terhadap Upaya Pencegahan Infeksi Nosokomial Di Rumah Sakit Kepresidenan Rspad Gatot Soebroto Tahun 2021 - Ganjar Gumelar Panghegar (2021)
The Global Health Security Agenda (GHSA) Forum stated that nosocomial infections are one of the health problems in many countries in the world, including Indonesia. Based on research conducted at 10 Teaching General Hospitals (RSU) in Indonesia, there are still nosocomial infection cases recorded around 6 - 16% with an average of 9.8% it can be occur at the Presidential Hospital of Gatot Soebroto RSPAD, where the The hospital is the main referral hospital for Army hospitals in Indonesia with high patient intensity and requires the skills of good medical workers. The purpose of this study was to determine of the correlation of medical worker's knowledge and attitude towards nosocomial infection prevention in Presidential Hospital RSPAD Gatot Soebroto 2021. This research was quantitative study with a cross-sectional study design. The sampling technique used accidental sampling with samples obtained by 330 medical workers, which is doctors and nurses. Data was collected using a online questionnaire (google form), the data was obtained and analyzed using the Chi-Square test α = 0.05. The results showed that knowledge (p-value = 0.006) and attitude (p-value = 0.037) with α = 0.05. There is have a relationship between knowledge and attitudes medical workers towards means to prevent nosocomial infections. It is hoped that medical workers will continue to implement efforts to prevent nosocomial infections and improve their own quality of knowledge and attitudes related to nosocomial infections.